Real-Time Optimized Error Protection Assignment for Scalable Image and Video over Wireless Channels - Muhit, Abdullah; Chuah, Teong Chee (BIRKHAUSER BOSTON INC, 2008)
A new error protection assignment scheme with applications to real-time wireless multimedia transmission is presented. The proposed scheme exploits the structure of scalable sources to ensure optimal assignment. This novel approach recasts the nonlinear optimization problem into a linear one, and then further remodels it into a discrete programming problem, thereby reducing the computational complexity dramatically. Furthermore, the proposed algorithm does not impose any requirement on the convexity of the source; i.e., it can equally be applied on a convex or nonconvex source. Results show that the described method facilitates a significant complexity reduction with respect to existing schemes, while exhibiting almost equivalent performance.